Ensinando pensamento computacional utilizando histórias em quadrinhos para alunos do ensino fundamental por meio de práticas mindfulness na disciplina de Educação Física - Souza, Felipe Faustino de (2021)
Education faces new challenges and, in response to this innovative scenario, changes that contemplate the training requirements reflect the current and future 21st century marketing and employability needs. In this way, it is necessary to develop skills for Basic Education listed by BNCC that are in agreement with the five skills for the 21st century (Critical Thinking, Collaboration, Creativity, Problem Solving and Computational Thinking) and in particular, Computational Thinking (CT), a skill classified as fundamental. In previous work on teaching CT and the use of Comics, the lack of attention was listed as one of the main difficulties, being related to the learning difficulties and Mindfulness practice points out improvements in attention, in social and emotional development. Therefore, the motivation for this dissertation is the need to prepare children and young people for a job market that is still uncertain, impacting on the need to develop the skills that are indispensable for the 21st century and, with this aim, this dissertation proposes the creation of evidence to verify the development of the PC with the use of comic books, in the discipline of Physical Education through Mindfulness practices for elementary school students. In order to achieve this objective, artifacts were elaborated and with the realization of the experiment with the participation of 26 students from the 6th to the 9th grade, with an average age of 13.69 for 5 weeks, it was possible to measure, on the CT test (CTt), the growth in the distribution of means in both groups, with a percentage of 9.86% for the experimental group and 5.37% for the control group. The results from the analysis referring to the Mindfulness test (MAAS) showed an increase in the distribution of means in both groups, experimental (4.44%) and control (2.7%). Although with the greatest increase for the experimental group, the small sample size negatively impacts statistical significance.